The state of the environment in Asia: 1999/2000 - Japan Environmental Council (Japan, Tokyo: Springer, 2000)
This book is the first attempt to report on the environmental problems in the Asian region, where serious effects of rapid economic growth have appeared recently. A wide range of topics in the fields of economics, law, biology and medicine is discussed, with detailed data analysis in cooperation between academic researchers and NGO groups throughout Asia